Motivating EFL Learners Comprehensively: Applying Dörnyei’s Taxonomy of Classroom Motivational Strategies - Raharja, Ernita; Ashadi, Ashadi (Journal of English Language Teaching and Linguistics, 2019)
Learning English as a foreign language is considered as a long-term process. During the period of learning, students might undergo ‘ups’ and ‘downs’ issue related to motivation swings. It is believed that motivated learners likely to outperform others who have high language aptitude but possess low motivation. For this reason, EFL teachers are required to involve strategies that captivate EFL students’ motivation. Motivating students should not only rely on immediate teaching strategies or a single activity since learning English as a foreign language is not an immediate process. Students tend to show fluctuated motivation in a time while in the other occasions could suffer in learning. Hence, how motivation is considered as a process rather than a single state is described. Examining other perspective about motivation and the changing of focus in researching motivation show that seeing motivation as a process indicates more promising results for EFL students’ learning accomplishment. Pointing out the importance of motivation in English learning attainment and the need of continuum process in motivating students, this paper offers the practical and comprehensive classroom motivational strategies by applying Dörnyei’s motivational taxonomy.